1996
DOI: 10.1103/physrevb.54.11322
|View full text |Cite
|
Sign up to set email alerts
|

Al-H and Al-D complexes in Si: A uniaxial-stress study of the hydrogen vibrational modes

Abstract: Perturbation of the 2201-cm Ϫ1 absorption line of the Al-H complex in Si by uniaxial stress is shown to be consistent with a stretching mode of a center with an effectively trigonal symmetry. Quantitative analyses of the effects of the stresses and of varying the temperature reveal the presence of a very-low-frequency transverse mode which transforms as the E irreducible representation in the trigonal symmetry. Its frequency is 64 cm Ϫ1 in the ground state of the stretching mode ͑representation A 1 ͒. An A 1 ϩ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 33 publications
2
16
1
Order By: Relevance
“…Two defects, B-H and Al-H, were investigated and it was found that E a Ϸ 0.2 eV for the B-H complex, 26 whereas E a = 0.37 eV for hydrogen bound to Al. 27 Obviously, of these two complexes, it is Al-H that has to be compared with isolated hydrogen since Al and Si are next neighbors in the Periodic Table. Indeed, in this case, the activation barrier for hydrogen reorientation in the Al-H complex is only 20% off from E a of isolated hydrogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two defects, B-H and Al-H, were investigated and it was found that E a Ϸ 0.2 eV for the B-H complex, 26 whereas E a = 0.37 eV for hydrogen bound to Al. 27 Obviously, of these two complexes, it is Al-H that has to be compared with isolated hydrogen since Al and Si are next neighbors in the Periodic Table. Indeed, in this case, the activation barrier for hydrogen reorientation in the Al-H complex is only 20% off from E a of isolated hydrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Such frequencies are typical for hydrogen-related defects in other semiconductors and characterize hydrogen vibrations. [24][25][26][27][28][29] The reorientation temperature, on the other hand, is very sensitive to the value of E a . From the data shown in the figure, we find that E a = 0.52± 0.04 eV.…”
Section: Frommentioning
confidence: 98%
“…At elevated temperatures a side-band shifted downwards in energy from the main line appears in the spectra [14]. Uniaxial stress also results in a side-band due to the coupling of the main mode with the thermally populated excited state [15]. The activation energies of the side-bands are in the range of 60-180 cm 1 -and seem to depend on the hydrogen isotope approximately as 1 m / [14,16].…”
Section: Discussionmentioning
confidence: 88%
“…The advantage of stress-induced dichroism stems from the fact that it allows to probe an elementary diffusion step—a jump between the two neighboring lattice sites. Indeed similar experiments performed for hydrogen-related defects in Si 22 _ 24 , GaAs 25 , 26 , ZnO 27 , 28 , and very recently In 2 O 3 29 provided a great deal of insight in the kinetics of hydrogen motion in these semiconductors.…”
Section: Introductionmentioning
confidence: 80%